THE ROLE OF THE POETRY "KALI MARTAPURA" IN EDUCATION - Putra, Muhammad Adhitya Hidayat; Malihah, Elly; Wiyanarti, Erlina; Darmawan, Wawan (International Conference On Social Science Education, 2023)
This study aims to describe and explain the role of satirical figures of speech and the educational value contained in the collection of poems "Malam Hujan" with the title of poetry “Kali Martapura” by Hijaz Yamani, namely the value of character education in learning in college. The technique of taking the research subject is a collection of Yemeni Hijaz poetry. This research uses purposive sampling. Then, the data collection technique uses purposive. The results of this study state that: (1) satire in poetry Hijaz Yamani there are 9 poems from 129 poems that act as satire against the authorities, satire on development, a satire on the economy, satire on the environment (2) The value of Character education in the Hijaz Yamani's poems are religious values, honesty, tolerance, hard work, democracy, and social care. (3) The role of satirical figures of speech and the value of character education.